Elita polityczna Ligi Polskich Rodzin (2001—2007) - Koziełło, Tomasz (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Political elite of League of Polish Families (2001—2007) The article analyzes political elites of League of Polish Families (LPR). The main target is demonstration, that real power in the party had group of people concentrated around Roman Giertych, chairman of Congress of LPR and president of party, descending from environment of All‑Polish Youth. That group achieved high position in the party, could subordinate executive powers and convert them on tool of realisation its interests. The effect that activity was lack of internal democracy in LPR and deprivation of executive powers real power for the few decision circle Key words: political elite, executive powers, tool of realisation of interests